Impact of HIV infection on treatment outcome of tuberculosis in Europe. (24th April 2016) - Karo, Basel; Krause, Gérard; Hollo, Vahur; van der Werf, Marieke J.; Castell, Stefanie; Hamouda, Osamah; Haas, Walter
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The effect of HIV on tuberculosis (TB) treatment outcomes has not been well established. We aimed to assess the impact of HIV infection on TB treatment outcomes by using data from notifiable disease surveillance in Europe. Methods: We analyzed the treatment outcomes of TB cases reported from nine European countries during 2010–2012. We investigate the effect of HIV on TB treatment outcomes using a multilevel and a multinomial logistic model, and considering the interaction between HIV and multidrug-resistant (MDR) TB. Results: A total of 61 138 TB cases including 5.5% HIV-positive were eligible for our analysis. In the multilevel model adjusted for age and an interaction with MDR TB, HIV was significantly associated with lower treatment success in all MDR strata [non-MDR TB: odds ratio (OR) 0.24 CI (confidence interval) 0.20–0.29; unknown MDR TB status: OR 0.26 CI 0.23–0.30; MDR TB: OR 0.57 CI 0.35–0.91]. In the multinomial regression model, HIV-positive cases had significantly higher relative risk ratio (RRR) for death (non-MDR TB: RRR 4.30 CI 2.31–7.99; unknown MDR TB status: 5.55 CI 3.10–9.92; MDR TB: 3.59 CI 1.56–8.28) and being 'still on treatment' (non-MDR TB: RRR 7.27 CI 3.00–17.6; unknown MDR TB status: 5.36 CI 2.44–11.8; MDR TB: 3.76 CI 2.48–5.71). We did not find any significant association between HIV and TB treatment failure (non-MDR TB: RRR 0.50 CI 0.15–1.67; unknown MDR TB status: 1.51 CI 0.86–2.64; MDR TB: 0.51 CI 0.13–1.87). Conclusion: This large study confirms that HIV is a strong risk factor for an adverse TB treatment outcome, which is mainly manifested by an increased risk of death and still being on TB treatment.